DETERMINAN KETERTARIKAN MAHASISWA DALAM MEMULAI KARIRMENJADI MARKETING PROFESIONAL - Listianto, Aris; Prasetya, Dimas Tri; Putri, Dila Ratnasari Catur; Yuliani, Nur Laila (Universitas Muhammadiyah Magelang, 2018)
This study aims to analyze the level of management students' interest in choosing acareer as a marketing professional. The main encouragement of this research is caused by theempirical study about the difficulty of finding work with limited employment, many peopleput aside work to become marketing, in other words marketing is not become a priority.Whereas, we know that marketing is the first step in starting a career in a company, becausemarketing is the spearhead of the company in introducing products to consumers. The sampleof this research consisted of 200 management students in sixth semester and managementstudents in eight semester who had taken marketing management courses. Based on theresults and discussion of this research, it can be concluded that self efficacy and technologyenvironment have a positive effect on students' interest in starting a career into marketing.While risk management, motivation, locus of control, and the social & cultural environmentdo not affect students' interest in starting a career into marketing.